Вeta1-Adrenoreceptors of the CA1 Area Mediate Morphine Modified State-Dependent Memory in Rat - Khajehpour, L.; Fathinia, K.; Moazedi, A.-A.; Kesmati, M. (Нейрофизиология, 2013)
In our study, we investigated the effects of intraCA1 microinjections of a selective b1 adrenoreceptor antagonist, betaxolol, on statedependent memory induced by morphine. A stepthrough passive avoidance task was used to assess memory retrieval. Male Wistar rats were bilaterally implanted with chronic cannulas in the CA1 regions of the dorsal hippocampus by stereotaxic surgery seven days before training. Each animal was tested 24 h after training to measure the stepthrough latency and the time spent in a dark chamber of the apparatus. Post-training intra-CA1 administrations of different doses of morphine (5 and 7.5 mg/kg, s.c.) decreased memory retrieval in the retention test (morphineinduced amnesia). The effect of posttraining injections of 7.5 mg/kg morphine on retrieval was reversed by pretest injection of the same dose of morphine. This phenomenon is named morphine statedependent memory. The results also showed that pre-test intra-CA1 microinjection of ineffective low doses of betaxolol (0.125 and 0.25 mg/rat) inhibited morphineinduced statedependent memory retrieval. Taken together, our results suggest that the CA1 may be potentially critical for morphine statedependent memory, and the b1adrenergic receptor mechanism(s) interact with the opioidergic system in the modulation of this type of memory in the CA1.